2014
DOI: 10.1209/0295-5075/107/26005
|View full text |Cite
|
Sign up to set email alerts
|

Is there a fractional breakdown of the Stokes-Einstein relation in kinetically constrained models at low temperature?

Abstract: We study the motion of a tracer particle injected in facilitated models which are used to model supercooled liquids in the vicinity of the glass transition. We consider the East model, FA1f model and a more general class of non-cooperative models. For East previous works had identified a fractional violation of the Stokes-Einstein relation with a decoupling between diffusion and viscosity of the form D ∼ τ −ξ with ξ ∼ 0.73. We present rigorous results proving that instead log(D) = − log(τ )+O(log(1/q)), which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…D now scales as τ −ζ where ζ relates to the characteristic spatio-temporal lengthscales involved in the hetergeneous dynamics, and a typical value has been found to be of about 0.82−0.85 for different glass formers [432,442,443]. Here, ζ has been proposed to derive from temperature dependent scaling exponents of both diffusivity and relaxation time, respectively [444].…”
Section: Stokes-einstein Breakdownmentioning
confidence: 99%
“…D now scales as τ −ζ where ζ relates to the characteristic spatio-temporal lengthscales involved in the hetergeneous dynamics, and a typical value has been found to be of about 0.82−0.85 for different glass formers [432,442,443]. Here, ζ has been proposed to derive from temperature dependent scaling exponents of both diffusivity and relaxation time, respectively [444].…”
Section: Stokes-einstein Breakdownmentioning
confidence: 99%
“…Diffusion of a probe particle in the East model was also studied rigorously in Ref. [10]. There it was found that in the limit very low temperature the inequality c 2 ≤ Dτ ≤ 1/c α holds, where α > 0 and c is the equilibrium concentration of excited sites, c = (1 + e 1/T ) −1 .…”
Section: Dimensional Dependence Of the Breakdown Of The Stokes-ementioning
confidence: 99%
“…When µ(η(0)) = 1/2, for ε small enough, the sign of the velocity can be read from (13). When µ(η(0)) = 1/2, the scenario is more subtle.…”
Section: 2mentioning
confidence: 99%
“…the ones considered in [24]. A further study of random walks in kinetically constrained models is given in [13].…”
Section: Introductionmentioning
confidence: 99%